FRW Viscous Fluid cosmological Model in f(R,T) Gravity (Global Journal of Science Frontier Research, 2013)
Friedmann-Robertson-Walker (FRW) space time is considered in f(R,T) gravity proposed by Harko et al. (Phys.Rev.D 84, 024020, 2011) when the source for energy momentum tensor is a bulk viscous fluid. A barotropic equation of state for the pressure and energy density is assumed to get a determinate solution of the field equations. Also the bulk viscous pressure is assumed to be proportional to energy density. A physical discussion of the model is also presented.
Keywords: FRW model - f (R; T) gravity - viscous fluid